2021
DOI: 10.3989/gya.0663201
|View full text |Cite
|
Sign up to set email alerts
|

Computational studies on physico-chemical properties in the quality analysis of corn and peanut oil

Abstract: Oils are commonly used in cooking as a frying medium which has been constantly subjected to different levels of heating. In this work, we have considered the most commonly used oils namely peanut oil and corn oil. Quality analyses of corn and peanut oils were made by relating macroscopic properties (ultrasonic velocity, viscosity, and density) to microscopic parameters (intermolecular free length, adiabatic compressibility etc.,) by subjecting them to six cycles of heating (190 ˚C). Variation in the mentioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The density values for the third and fourth frying cycles were higher than the control, indicating a progressive increase in density as the oil underwent repeated frying. This observation aligns with the findings reported by Valantina & Jayalatha [17] who also noted an increase in the density of CO after multiple heating cycles. Additionally, Kalogianni [46] suggested that the number of frying cycles had a significant impact on oil density.…”
Section: Free Fatty Acids (Ffa)supporting
confidence: 93%
See 1 more Smart Citation
“…The density values for the third and fourth frying cycles were higher than the control, indicating a progressive increase in density as the oil underwent repeated frying. This observation aligns with the findings reported by Valantina & Jayalatha [17] who also noted an increase in the density of CO after multiple heating cycles. Additionally, Kalogianni [46] suggested that the number of frying cycles had a significant impact on oil density.…”
Section: Free Fatty Acids (Ffa)supporting
confidence: 93%
“…The density of CO was precisely measured using a pycnometer in accordance with ASTM standard method D891-09 (American Society for Testing and Materials) [17].…”
Section: Densitymentioning
confidence: 99%